2014
DOI: 10.1007/s00018-014-1806-x
|View full text |Cite
|
Sign up to set email alerts
|

Syk is indispensable for CpG-induced activation and differentiation of human B cells

Abstract: B cells are efficiently activated by CpG oligodeoxynucleotides (ODNs) to produce pro-inflammatory cytokines and antibody (Ab). Here, we describe a so far unidentified, spleen tyrosine kinase (Syk)-dependent pathway, which is indispensable for CpG-induced human B cell activation. We show that triggering of B cells by CpG results in Syk and src kinase phosphorylation, proliferation, as well as cytokine and Ab production independent of the BCR. Notably, all these functions are abrogated when Syk is inhibited. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…This data is consistent with previous reports demonstrating that Syk kinase is essential for mediating NK cell killing function [31]. While a majority of the TLR signaling pathways are mediated by IRAK4 kinase [32], we observed that inhibitors of other kinases such as PI3Kδ, SYK/ZAP-70 and JAK also have an impact on functional TLR responses, consistent with previous reports [3335]. Among the TLR responses evaluated, cyclosporine, PI3Kδ and SYK/ZAP70 inhibitors inhibited TLR3 and TLR9, but not TLR7 induced responses.…”
Section: Discussionsupporting
confidence: 93%
“…This data is consistent with previous reports demonstrating that Syk kinase is essential for mediating NK cell killing function [31]. While a majority of the TLR signaling pathways are mediated by IRAK4 kinase [32], we observed that inhibitors of other kinases such as PI3Kδ, SYK/ZAP-70 and JAK also have an impact on functional TLR responses, consistent with previous reports [3335]. Among the TLR responses evaluated, cyclosporine, PI3Kδ and SYK/ZAP70 inhibitors inhibited TLR3 and TLR9, but not TLR7 induced responses.…”
Section: Discussionsupporting
confidence: 93%
“…The proximal BCR-signalosome molecules, Syk and Btk, have been associated with TLR7/TLR9 activation (3739). In human B cells, Syk appears to be a positive regulator of TLR and TLR–BCR synergism, since inhibition of Syk blocks TLR responses (40, 41). The role of Btk in BCR–TLR signaling is less clear.…”
Section: Proximal Bcr-signaling Components Important For Tlr7/tlr9 Aumentioning
confidence: 99%
“…While not yet studied directly in B cells, the molecular mechanism may be similar to that found in dendritic cells, where Lyn directly associates with IRF5 and in doing so, inhibits the ability of TRAF6 to associate with and activate the transcription factor (55). Syk is a positive regulator of TLR signaling (40, 41). Syk activation has been associated with TRAF6 expression in B cells from patients with SLE (38).…”
Section: Bcr and Tlr7/tlr9 Signaling Cascades: Crosstalk And Potentiamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that many signaling pathways induce Syk phosphorylation, such as BCR, TLR, and BAFF signaling pathways [41][42][43][44]. Notably, BCR, TLR, and Bcell activating factor signaling are highly activated in B cells from SLE patients and lupus-prone mice [45][46][47][48].…”
Section: Ifn-α In Sle Pathogenesismentioning
confidence: 99%